The chemical synthesis of the anticodon loop of an eukaryotic initiator tRNA containing the hypermodified nucleoside N6-/N-threonylcarbonyl/-adenosine/t6A/1. - Adamiak, R W (1978)
In this work, the first example of chemical synthesis of oligoribonucleotide containing the hypermodified nucleoside N6-/N-threonylcarbonyl/-adenosine /t6A/ is presented. Synthesis of the heptamer C-C-C-A-U-t6A-A IX, the sequence of which is related to the anticodon loop of the initiator tRNA from yellow lupine, was achieved by: /i/ phosphotriester block synthesis of suitably protected heptamer VI containing an adenosine unit with a free exo-NH2 group, /ii/ highly effective "one-flask" procedure for the transformation of the free exo-NH2 group of adenosine unit of heptamer VI into a N,N'-disubstituted urea system of t6A of heptamer VII /hypermodification/, and /iii/ final deprotection of VIII /32% total yield/ with the use of a new approach for simultaneous hydrogenolysis /PdO-hydrogen-pyridine/ of the p-nitrobenzyl group and 2,2,2-trichloroethyl groups from carboxyl function of t6A and internucleotide phosphates respectively.